QUALITY TESTING OF FROZEN COOKED TUNA (Thunnus albacares) LOINS - Rafli Muhammad Syah Zalukhu; Mohammad Sayuti; Randi B.S Salampessy (Aurelia Journal, 2023)
Tuna is a type of fish that is very popular with the people of Indonesia and abroad. There are many types of tuna products or preparations, including frozen cooked tuna loin. This study aimed to determine the quality of frozen cooked tuna loin. Quality testing of raw materials and frozen cooked tuna loin products include organoleptic, microbiological (Total Plate Count, Escherichia coli, Coliform, Staphylococcus aureus, Vibrio parahaemolyticus, and Salmonella), chemical (histamine) tests, as well as observing the application of cold chain, yield and productivity. Organoleptic test results for raw materials and frozen tuna loin products showed the same value, namely 8. Microbiological test results for frozen tuna ALT 4.9 x 103, E. coli <3, Coliform <3, S. aureus <3, Salmonella negative and V. parahaemolyticus negative. Microbiological test results of frozen cooked tuna loin were E. coli, Coliform <3, S. aureus, V. parahaemolyticus negative and Salmonella negative. The histamine content of the raw material was 2.2 ± 0.6 ppm, while the final product of frozen cooked tuna loin was 3.48 ± 0.72 ppm. The average yield at the weeding stage was 89%, cooking 81%, deheading 60.7%, skinning 50.4%, and cleaning 38.3%. The average productivity of employees at the butchering stage is 324.47 kg/hour/person, the deheading and skinning stages are 43.55 kg/hour/person, and the loining and cleaning stages are 7.06 kg/hour/person. Overall, frozen cooked tuna loin products meet the SNI standard for Frozen Cooked Tuna Loin (7968:2014).